Seeds for Diversity and Inclusion Agroecology and Endogenous Development - Nishikawa, Yoshiaki; Pimbert, Michel (Springer Nature, 2022)
This open access book will contribute to a more nuanced debate around seed system resilience that goes beyond the dominant dichotomous conceptualization of seed governance often characterized as traditional vs modern, subsistence vs commercial, or local vs global. While reflecting on the expanding oligopoly in the current seed system, the authors argue that such classifications limit our ability to critically reflect on and acknowledge the diverse approaches through which seed governance is practiced around the world, at various scales, creating a mosaic of dynamic complementarities and autonomies. The authors also highlight the importance of this much needed dialogue through case studies of seed governance approaches and practices found in and around Japan.